Contribución a la mejora de los procesos administrativos de la Dirección de Talento Humano de la ESPAM MFL - Rendón Loor, Hober Isrrael (2018)
At present the companies and state institutions use processes to facilitate the orientation of functions, Seeking as an to reduce the cost and to maximize the quality or efficiency of either goods or service, This work is aimed at contributing to the improvement of the administrative processes of the Human Talent Direction of ESPAM MFL, Using as a technique the matrix of value Added Analysis (AVA) of the processes, Proposed by Loor and Molina, starting in the first instance with a diagnosis where an interview was made to the Human Talent Director, who provided information of the processes that are carrier out and those responsible, also made direct observation of the activities, Proceeding to draw up an observation form and then proceed to the elaboration of the processes with As-Is, techniques, then the AVA was executed in two work sessions, resulting in a very low added value (VAT), and that is to say, deficient, In which it became evident that the majority of activities are preparation and archiving. In conclusión, It is specified that with the implementation of the improvement plan it will be possible to increase the value adding activities and at the same time in the case of one of the processes, the correct flowchart will be visualized, since it did not exist digitally or physically, And thus obtains an increase in the index of the added value of the processes, Which favors the management and the strengthening of the institution as such.